Managing Village Enterprises Effectively Boosts Community Welfare in Indonesia: Mengelola Usaha Desa Secara Efektif Meningkatkan Kesejahteraan Masyarakat di Indonesia - Moh Syahrul Ramadhina; Isna Fitria Agustina (Academia Open, 2024)
This research investigates the effectiveness of managing Village-Owned Enterprises (BUMDes) in improving community welfare in Kemiri Village, Sidoarjo. Using a qualitative method with a descriptive approach, data were collected through interviews and direct observations. The study evaluates BUMDes management using three indicators: goal achievement, integration, and adaptation. Results show that while income for food court stand owners has increased, it still depends on event frequency. Integration efforts are hampered by irregular socialization activities due to new management. However, communication is effective through accessible contacts and social media. Adaptation efforts are supported by the community, benefiting from affordable food and essential goods. The study highlights the need for structured socialization schedules and improved funding to optimize BUMDes' impact on community welfare. Highlight: Income rise tied to event frequency. Socialization lacks regular schedule. Easy communication via contacts, social media. Keyword: Village-Owned Enterprises, community welfare, qualitative research, BUMDes management, economic impact